DETERMINING THE COST OF PRODUCTION IN SETTING THE SELLING PRICE WITH THE FULL COSTING METHOD ON MSME SUMPIA DUA UDANG - Nurdilasari, Siti; Djadjuli, M; Tatmimah, Itat; Muzayyanah, Muzayyanah; Indriyani, Rinni (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2021)
The purpose of this study was to identify and introduce the determination of the cost of goods manufactured and the cost of goods sold using the full costing method at UMKM Sumpia Dua Udang. This research was conducted at UMKM Sumpia Dua Udang in Kubang Village. This study uses a qualitative method. The results showed that the Sumpia Dua Udang UMKM in calculating the cost of production of UMKM still carried out the traditional method, did not charge all costs and had not calculated costs in detail during the production process such as factory overhead costs. By using the full costing method, the cost of goods sold is lower than the traditional method, which is Rp 20,418,389, the cost of goods sold using the full costing method is Rp 20,716,389 and the selling price using the full costing method is higher than the traditional method which is Rp 88,470. Keywords: Cost of Production, Cost of Goods Sold, Selling Price and Full Coting